The Influence Of Product Innovation And Brand Image On Purchasing Decisions On Koala Iced Tea Drinks, Talasalapang Branch, Makassar City - Firda Nurhidayah; Moh. Aris Pasigai; Sherry Adelia (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to analyze the effect of product innovation and brand image on purchasing decisions for koala ice tea drinks, Talasalapang branch, Makassar City. The sample in this study amounted to 55 people. The type of research used is quantitative with a descriptive approach. Based on the results of this study, it shows that the t test results obtained on the product innovation variable (X1) on purchasing decisions (Y) obtained t count 1.925> t table 0.260 with a significance level of 0.060 which means H1 is accepted, while for the brand image variable (X2) on purchasing decisions (Y) obtained t count 3.151> t table 0.260 with a significance level of 0.003 which means H2 is accepted. Based on the results of the research conducted, it can be known and proven that the variables of purchasing decisions and brand image have a significant influence on purchasing decisions for koala ice drinks at the Talasalapang branch in Makassar City.